2014
DOI: 10.5423/ppj.oa.09.2013.0093
|View full text |Cite
|
Sign up to set email alerts
|

Oak Tree Canker Disease Supports Arthropod Diversity in a Natural Ecosystem

Abstract: Microorganisms have many roles in nature. They may act as decomposers that obtain nutrients from dead materials, while some are pathogens that cause diseases in animals, insects, and plants. Some are symbionts that enhance plant growth, such as arbuscular mycorrhizae and nitrogen fixation bacteria. However, roles of plant pathogens and diseases in natural ecosystems are still poorly understood. Thus, the current study addressed this deficiency by investigating possible roles of plant diseases in natural ecosys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…may strongly attract fungivorous insects and affect their community structure. Lee et al [56] reported that stem canker caused by Annulohypoxylon truncatum (Xylariaceae) on oak stem significantly increases invertebrate diversity in Korea, irrespective of the presence or absence of sap flow.…”
Section: Discussionmentioning
confidence: 99%
“…may strongly attract fungivorous insects and affect their community structure. Lee et al [56] reported that stem canker caused by Annulohypoxylon truncatum (Xylariaceae) on oak stem significantly increases invertebrate diversity in Korea, irrespective of the presence or absence of sap flow.…”
Section: Discussionmentioning
confidence: 99%